Ginkgolide C alleviates atherosclerosis by activating LAMP-2A to enhance chaperone-mediated autophagy and promote NLRP3 inflammasome degradation - Zhang, Rui (Frontiers in Pharmacology, 2025)
IntroductionThe NLRP3 inflammasome/IL-1β-dependent inflammatory response serves as a critical factor and key trigger in exacerbating atherosclerosis (AS), whereas chaperone-mediated autophagy (CMA) recognizes and degrades the NLRP3 inflammasome. Targeting this pathway represents a more nuanced and targeted anti-inflammatory strategy to mitigate AS progression. As a key bioactive component derived from Ginkgo biloba leaves, Ginkgolide C (GC) possesses notable anti-inflammatory effects and confers protection against myocardial and cerebral ischemia-reperfusion injuries. The current research aimed to investigate whether GC could exert protective effects against AS and to elucidate its potential underlying mechanisms.MethodThis study established both in vivo (high-fat diet/vitamin D3-induced atherosclerotic mouse model) and in vitro (LPS/ATP-stimulated RAW264.7 macrophage injury model) systems. In vivo evaluations included: H&E and Oil Red O staining for atherosclerotic lesion assessment; biochemical detection for lipid profiles; transmission electron microscopy for autophagic structure observation; immunohistochemistry and immunofluorescence for CMA regulator (LAMP-2A), NLRP3 inflammasome as well as key pro-inflammatory cytokines such as IL-1β, IL-18, and TNF-α. In vitro analyses comprised: MTT assay for cell viability; ELISA for quantifying inflammatory cytokine secretion; Western blotting for LAMP-2A, NLRP3 inflammasome, and NF-κB, MAPK signaling pathways molecules. LAMP-2A knockdown was conducted using siRNA to validate the CMA-dependent mechanisms underlying GC’s effects.ResultOur results demonstrate that GC potentiated CMA activity in macrophages, leading to promoted degradation of the NLRP3 inflammasome via the lysosomal pathway. This process effectively suppressed the NLRP3 inflammasome/IL-1β-driven inflammatory cascade, ultimately attenuating atherosclerotic progression.ConclusionGC alleviates AS via a novel LAMP-2A-dependent mechanism that enhances protein clearance and suppresses NLRP3 inflammation, providing a targeted alternative to broad immunosuppression. These results establish GC as a promising therapeutic candidate and prompt further studies on its clinical efficacy and applicability in other chronic inflammatory diseases.